Partial Least Squares Method for Simultaneous Spectrophotometric Determination of Four Food Pigments - Dong, Xiongzi; Wang, Liping; Tian, Yan; Si, Shengzhu (Asian Journal of Chemistry, 2010)
Due to the strong overlapping of absorption spectra, the simultaneous determination of four food pigments mixtures (amaranth, carmine, enticed red, pyrosine) by using spectrophotometric method is difficult. A chemometrics method, partial least squares (PLS), was described for the simultaneous determination of four pigments in synthetic samples. Spectra of mixtures of four food pigments between 380-640 nm wavelengths by 0.2 nm intervals were recorded, in the range of concentrations comprised between 1-8 μg mL-1 for amaranth, carmine, enticed red and 0.5-4 μg mL-1 for pyrosine, respectively. The analyte recoveries from synthetic mixtures range from 100.26 to 103.24 % for amaranth, from 93.677 to 113.03 % for carmine, from 95.749 to 99.448 % for enticed red and from 85.446 to 104.33 % for pyrosine, respectively. The root mean square difference (RMSD) for the four analytes are 0.052772, 0.079997, 0.088947, 0.061912, respectively. The result shows that PLS is an efficient chemometrics method applied for prediction of the four analytes.